The EU common fisheries policy law and practice - Churchill, R. R. (Robin Rolf); Owen, Daniel, 1966- (Oxford : Oxford University Press, 2010)
The Common Fisheries Policy (CFP) is widely blamed both for the poor state of Europe's fish stocks and the woes of its fishermen. This book lays out in detail the varied roles and responsibilities of the EU under the CFP,examining both the law and the policy issues crucial to understanding its operation.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Fishery policy -- European Union countries; Fishery law and legislation -- European Union countries; Industry; Industry & industrial studies